Shaded Relief Geological Map of the South Polar Region of the Moon - Allender, E. J.; Orgel, C.; Almeida, N. V.; Cook, J.; Ende. J. J.; Kamps, O.; Mazrouei, S.; Slezak, T. J.; Soini, A.-J.; Kring, David A. (David Allen); orcid:0000-0002-3440-6282 (Lunar and Planetary Institute, 2020)
This map is based on the geology of Spudis et al. (2008). The map is overlain on data collected by the Lunar Orbiter Laser Altimeter (LOLA) on the Lunar Reconnaissance Orbiter (LRO). The data are the LOLA hillshade with solar azimuth 45°W and solar elevation 45° derived from a LOLA 20-m elevation product (NASA Goddard Space Flight Center; Smith et al., 2010, 2017). The map encompasses the region around the lunar south pole, which lies on the rim of Shackleton crater, and includes Sverdrup, Slater, de Gerlache, Cabeus, Haworth, Shoemaker, and Faustini craters. The map extends north onto the nearside of the Moon beyond Mons Malapert, also known as the Malapert massif. Spudis et al. (2008) mapped Shackleton crater with a 3.6 Ga Imbrian age, although Wilhelms et al. (1979) previously mapped it with an Eratosthenian age (~1.1 to 3.3 Ga), and, more recently, Zuber et al. (2012) and Tye et al. (2015) reported Imbrian ages of ~3.69 Ga, and 3.51(+0.05,-0.08) Ga, respectively, with the understanding that some surfaces within Shackleton have been modified by younger geologic processes. As mapped by Spudis et al. (2008), Shoemaker and Faustini have Nectarian ages, but Tye et al. (2015) report pre-Nectarian ages like that of Haworth. See the map for bibliographic details. Center for Lunar Science and Exploration is a product of the 2016 Exploration Science Summer Intern Program: E. J. Allender, C. Orgel, N. V. Almeida, J. Cook, J. J. Ende, O. Kamps, S. Mazrouei, T. J. Slezak, A.-J. Soini, and D. A. Kring